Explaining international differences in rates of overeducation in Europe - Maria A. Davia; Seamus McGuinness; Philip J. O'Connell (The Economic and Social Research Institute (ESRI), 2010)
This paper examines the factors determining variations in international rates of overeducation. We find significant effects for a range of factors including labour market structural imbalances, risk, trade-union density and the structure of academic funding. The results suggest that international levels of overeducation are particularly sensitive to variations in higher education funding arrangements.
Keywords: 330; overeducation; international variation; mismatch